Alterations in chlorophyll a fluorescence, pigment concentrations and lipid peroxidation to chilling temperature in coffee seedlings - Oliveira, Jurandi Gonçalves de; Aguiar Alves, Pedro Luís da Costa [UNESP]; Vitória, Angela Pierre (Elsevier, 2009)
Coffea arabica L. is considered to be sensitive to low temperatures throughout its life cycle. In some Brazilian regions, seedling production occurs under shade conditions and during the winter, with average temperatures of around 10 °C. The formation and functioning of the photosynthetic apparatus are strongly controlled by temperature. This study aimed to assess the changes that occurred in pigment contents, lipid peroxidation and variables of chlorophyll a fluorescence during the greening process of coffee seedlings submitted to chilling. Results indicate that saturation of the photosynthetic activity of coffee seedlings occurred before saturation of the accumulation of chloroplastid pigments. Pigment accumulation during the greening process is far beyond the metabolic needs for the maintenance of photosynthetic activity, more specifically of photosystem II. Coffee seedlings attained a quantum yield equivalent to that of the control with approximately half the chlorophyll a and b contents and around 40% of the carotenoid. Low temperature decreases the metabolism of seedlings, consequently reducing free radical production and lipid peroxidation. The chilling temperature (10 °C) used inhibited the accumulation of chloroplast pigments, in turn altering the capacity of the photosynthetic tissue of etiolated coffee seedlings to capture and transfer photon energy to the photosystem II reaction centre. These alterations were better demonstrated by O-J-I-P chlorophyll a fluorescence transients, rather than F v/F m and F v/F 0 ratios. © 2009 Elsevier B.V. All rights reserved.
Keywords: Chlorophyll a fluorescence transient O-J-I-P; Coffea arabica L.; Environmental stress; Photosynthetic pigments; Photosystem II quantum yield; carotenoid; chlorophyll a; chloroplast; coffee; concentration (composition); environmental stress; lipid; photosynthesis; seedling; temperature effect; Coffea arabica; Viridiplantae